Pengaruh Kompetensi SDM terhadap Komitmen Organisasional, Kompensasi dan Kinerja Karyawan (Studi Pada Perusahaan Jasa Konstruksi Bersertifikasi ISO-9000 di Provinsi Sulut) - Rumawas, Wehelmina (Jurnal Aplikasi Manajemen, 2011)
The aims of this research are: 1) to analyze and explain the significant influence of human resource variable on organizational commitment. 2) to analyze and explain the significant influence of human resource variable on compensation. 3) to analyze and explain the significant influence of human resource competence variable on employee's performance. 4) to analyze and explain the significant influence of organizational commitment on to compensation. 5) to analyze and explain the significant influence of organizational commitment toward employee's performance. 6) to analyze and explain the significant influence of compensation variable on employee's performance. This research samples 211 field employees. The data is sampled using propotional random sampling. Questioner is the main instrument to collect data, as well as to obtain secondary data of the related company. SEM (Structural Equation Model) is used to calculate and test research result data. Research result shows that: 1) Significant and positive influence of human resource competence on organizational commitment is strongly seen. 2) Significant and positive influence between human resource competence toward compensation is strongly seen. 3) Significant and positive between human resource competence and employee's performance is strongly seen. 4) Significant and positive influence between organizational commitment toward compensation is strong, 5) Significant and positive influence between organizational commitment toward employee's performance. 6) Significant and positive influence between compensation toward employee's performance.